Formulate metal-binder mixture for room temperature casting - Wong, Shi Kar (2024)
Addressing persistent challenges in the foundry industry, such as energy consumption and air pollution, this project explores room-temperature metal casting. This innovative project suspends metal powder in a binder solution to form a castable form, eliminating the need for traditional foundries. The procesx is followed by the therimal treatment, including debinding and sintering, to produce the final article. The objectives of this projects including figure out the optimized independent variables, and study the mechanical properties and rheological behaviour of the slurry. Reusable silicone or 3D printed resin molds significantly cut mold production time and metal melting enrgy use. The experiment procedure, including mixing metal powder with binder, homogenizing the mixture, pouring it into silicone molds, conducting tests, curing the cast product, and finally analyzing the samples' internal structures using a scanning electron microscope (SEM). The Taguchi Method optimizes the metal mix to reduce defects, with tests on mechanical properties like density, hardness, and rheology confirming the ink's quality. In conclusion, the optimize formulation of 60 wt% of 17-4PH metal, 1.5 wt% of binder and 6 wt% of plasticizer show a non-newtonian flowable slurry mixture and casted in silicone mould. In which the green article formed has the insignificant porosity and good surface finishing. The article is then process under debind temperature of 210 deg and vavuum sintered of 1350 deg to form a final article which has a density > 90% and average hardness of 207 HV. This has demonstrated that this method present a more suitable rapid casting solution compared to traditional sand casting method.